Managemen Keuangan Guru Honorer Dalam Menunjang Proses Pembelajaran di Masa Pandemi Covid-19 - Fazriyah Ayu Nuzula; Ahmad Syarif (EduInovasi: Journal of Basic Educational Studies, 2022)
The purpose of this study was to identify obtaining information about the experience of honorary teachers on financial income during the Covid 19 pandemic. The study used an exploratory case study method and the research approach used a qualitative case study method used to obtain information on the experience of honorary teachers on financial income during the pandemic. Covid 19. In this study, respondents were 4 honorary teachers and 1 principal in Bogor. For confidentiality purposes, respondents were given the initials R1, R2, R3, R4, R5. Semi-structured interviews were conducted and a list of questions compiled for interviews was developed based on related literature. Respondents for this study were honorary teachers and school principals. The results of this study are that there are several obstacles experienced by honorary teachers during the Covid-19 pandemic, namely the experience of honorary teachers with distance learning during the Covid-19 pandemic, the financial income of honorary teachers during the Covid-19 pandemic and the financial management of honorary teachers in the future. the Covid-19 pandemic Keywords: Experience, honorary teachers, management, finance, the Covid-19 pandemic